Detection of Streptococcus gallolyticus and Four Other CRC-Associated Bacteria in Patient Stools Reveals a Potential “Driver” Role for Enterotoxigenic Bacteroides fragilis - Périchon, Bruno; Lichtl-Häfele, Julian; Bergsten, Emma; Delage, Vincent; Trieu-Cuot, Patrick; Sansonetti, Philippe; Sobhani, Iradj; Dramsi, Shaynoor (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus gallolyticus subspecies gallolyticus (Sgg) is an opportunistic pathogen causing invasive infections in the elderly and its presence in human blood is often associated with asymptomatic colon neoplasia. Prevalence of Sgg in the stools of patients with normal colonoscopy (control) was compared to patients with colorectal adenomas (CRA) or with carcinomas (CRC) from stage I to IV. Presence of other CRC associated bacteria such as toxicogenic Bacteroides fragilis, Fusobacterium nucleatum, Parvimonas micra and pks island encoding colibactin was also investigated. Fecal samples collected in France between 2011 and 2016 from patients with normal colonoscopy (n=25), or with adenoma (n=23) or colorectal cancer at different stages (n=81) were tested by PCR for presence of Sgg, B. fragilis, F. nucleatum, P. micra, and pks island. Relative quantification of Sgg, F. nucleatum and P. micra in stools was performed by qPCR. Sgg prevalence was significantly increased in the CRC group. Our results also revealed (i) a strong and significant increase of toxinogenic B. fragilis in the patients at early adenoma stage and of pks island at late stage of CRC and (ii) increased levels of F. nucleatum and P. micra in stools of CRC patients. Furthermore, simultaneous detection of these five bacterial markers was only found in the group of CRC patients. Our results indicate that prevalence or relative level of the CRC- associated bacteria varies during CRC development. Among them, B. fragilis (bft +) singled-out as the sole pathobiont detected at early adenoma stage.